Why we need to re‐define long‐term success for people living with HIV. (15th March 2023) - Fuster‐RuizdeApodaca, Maria J.; Wohl, David A.; Cascio, Mario; Guaraldi, Giovanni; Rockstroh, Jürgen; Hodson, Matthew; Richman, Bruce; Brown, Gina; Anderson, Jane; Lazarus, Jeffrey V.
Abstract: Over the past few decades, the life expectancy of people living with HIV has markedly improved due to the advances in HIV diagnosis, linkage to care, and treatment. However, with these advances, a new set of challenges has emerged that must be addressed to ensure the long‐term well‐being of people living with HIV. In this article, as part of a wider journal supplement, we explore the unmet needs and challenges across the HIV continuum of care and re‐define what long‐term success looks like to support the healthy ageing of all people affected by HIV.